Ekonometride Güncel Yöntemler ve Uygulamalar Prof. Dr. Ahmet M. Gökçen'e Armağan - Cil, Nilgun (Istanbul University Press, 2021)
This book, which we present to our dear readers, is special in two aspects. The first is that this book includes studies prepared by the academic members and assistants who continue their academic activities in various universities of our country, on the developments and applications in the fields of econometrics and its components, statistics, and operations research. The studies including current issues in the field of econometrics, which is a dynamic and advancing discipline, are a guide for academicians and postgraduate students who want to apply empirical analyses. Another feature of the book is that it is dedicated to our valuable teacher, Prof. Dr. Ahmet M. GÖKÇEN. He graduated from Istanbul University, Faculty of Economics in 1968, became a research assistant in the same faculty in 1972, an Associate Professor in 1982, and a Professor in the field of econometrics in 1988. He led the establishment of econometrics departments in our country and the inclusion of the econometrics course in the curricula of our Economics and Finance Departments, along with Prof. Dr. Ahmet KILIÇBAY. Prof. Dr. Ahmet M. GÖKÇEN has taught Quantitative Economics and Econometrics at the Faculty of Economics for many years and has numerous published articles. Along with being a faculty member, he has worked in various administrative levels at Istanbul University and government throughout his career. He served as Undersecretary of the Ministry of Energy and Natural Resources between 1993-1996 and as the Minister Counselor of the Ministry of Transportation and the Ministry of State between 1986-1992. He served as a board member of Karadeniz Copper Enterprises (1989-1990), Ereğli Iron and Steel Factories (1989-1990), and HAVAŞ (1988-1998). Our professor, who served as the head of the Department of Econometrics of the Faculty of Economics for many years also took part in various boards of the Faculty of Economics during this period. Working at various administrative levels in Istanbul University, he has been the Director of the Computer Application and Research Center (1996-2007; 2009-2011) and Director of the Social Sciences Institute (2005-2007). Between 2009-2011, he served as the Vice Rector of Istanbul University and retired in 2011. Prof. Dr. Ahmet M. GÖKÇEN continues working as the Vice Rector of Rumeli University and Dean of the Faculty of Economics and Administrative Sciences. In addition to his academic support, he became a model in human relations for us with his kindness and style and will continue influence us in our memories.